2002
DOI: 10.2223/jped.664
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in children under 3 years of age in public day care centers

Abstract: Objective: to study the prevalence of anemia in children aged less than 36 months in public day care centers in the city of Cuiabá, state of Mato Grosso, Brazil.Methods: cross-sectional study with all children (n=271) less than 36 months of age who attended public day care centers in mid-1997. Children were evaluated as to their hemoglobin levels (venous blood, analyzed at the Central State Laboratory) and anthropometric indicators (weight/age, height/age, weight/height).Results: a high prevalence (63%) of ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…The prevalence of anemia in the present study (29.3%) was similar to that found by Almeida et al [22] in 184 children aged between 12 and 59.9 months who were cared for on a full-time basis in five day-care centers in the city of Jardinópolis, state of São Paulo, but different from that found in other studies of children in day-care centers [4,5,14,23].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prevalence of anemia in the present study (29.3%) was similar to that found by Almeida et al [22] in 184 children aged between 12 and 59.9 months who were cared for on a full-time basis in five day-care centers in the city of Jardinópolis, state of São Paulo, but different from that found in other studies of children in day-care centers [4,5,14,23].…”
Section: Discussionsupporting
confidence: 76%
“…In Brazil, according to a recent meta-analysis, anemia is considered to be a serious public health problem, affecting 53% of children under 5 years of age [3]. Regional studies in Brazil confirm the high prevalence of anemia; a study conducted in day-care centers of the city of Cuiabá among 271 children younger than 36 months found a prevalence of anemia of 63% [4], and a study conducted in day-care centers of São Paulo among 330 children aged between 6 and 75 months found a prevalence of 68.8% [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is a cross sectional study carried out in 2008 including 100 children less than 5 years old who attended three public day care centers in the city of Cuiabá, a city located in the Center-West region of Brazil, state of Mato Grosso, with an estimated population of 569.830 inhabitants. A previous study showed high prevalence (63%) of anemia among children aged less than 36 months in public day care centers of Cuiabá 10 .…”
Section: ▄ Materials and Methodsmentioning
confidence: 91%
“…Historically, there have been difficulties obtaining permission from private institutions to conduct studies on their premises. This has meant that the picture of nutritional status of children has been partial since higher social economic classes were underrepresented, given that only children from the less privileged social economic classes tend to go to public daycare centers (27) . In this study, it was found that the dietary intakes of children at public and private day care centers did not in general differ in terms of energy, macronutrient and micronutrient content.…”
Section: Discussionmentioning
confidence: 99%